2021
DOI: 10.1186/s12874-021-01338-2
|View full text |Cite
|
Sign up to set email alerts
|

Need of care in interpreting Google Trends-based COVID-19 infodemiological study results: potential risk of false-positivity

Abstract: Background Google Trends (GT) is being used as an epidemiological tool to study coronavirus disease (COVID-19) by identifying keywords in search trends that are predictive for the COVID-19 epidemiological burden. However, many of the earlier GT-based studies include potential statistical fallacies by measuring the correlation between non-stationary time sequences without adjusting for multiple comparisons or the confounding of media coverage, leading to concerns about the increased risk of obta… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(25 citation statements)
references
References 20 publications
0
25
0
Order By: Relevance
“…Besides, genuine interest on self-symptoms before they become broadly known to the general public may have faded [ 17 ]. Prior studies have found that Google searches for smell and taste loss varied between countries [ 27 ] but remained at a higher level after the beginning of the pandemic [ 27 , 28 ]. In our study, searches for smell and taste disorders showed visually better prediction among citizens than HCPs, possibly indicating that loss of smell or taste may have been the only concerning symptom of mild COVID-19 cases.…”
Section: Discussionmentioning
confidence: 99%
“…Besides, genuine interest on self-symptoms before they become broadly known to the general public may have faded [ 17 ]. Prior studies have found that Google searches for smell and taste loss varied between countries [ 27 ] but remained at a higher level after the beginning of the pandemic [ 27 , 28 ]. In our study, searches for smell and taste disorders showed visually better prediction among citizens than HCPs, possibly indicating that loss of smell or taste may have been the only concerning symptom of mild COVID-19 cases.…”
Section: Discussionmentioning
confidence: 99%
“…Although this influence may jeopardize the adoption of Google Trends in many research areas, it remains suitable for conducting infodemiological investigations; in fact, if certain conditions are met (ie, high internet penetration, high Google use, and data set stability), the relative search volumes (RSVs) on Google Trends faithfully reflect the interests of a population [ 25 ]. Moreover, Sato et al [ 29 ] proposed a new method to evaluate, quantify, and eliminate the media disturbance in data sets.…”
Section: Introductionmentioning
confidence: 99%
“…To achieve our goal, we used Google Trends, an online tool developed by Google that allows the user to monitor netizens' web interests in specific keywords, queries, and topics. Specifically, Google Trends has been used successfully in several infodemiological studies; however, its results need to be interpreted cautiously and examined through appropriate methodologies 18,19 . In this regard, this paper also has two secondary purposes: the first is to provide a new procedure to improve the sensitivity and accuracy of Google Trends datasets, while the second is to provide a keyword collection methodology suitable for representing the vast majority of COVID-19-related queries.…”
Section: Research Objectivesmentioning
confidence: 99%